2017
DOI: 10.1111/jicd.12275
|View full text |Cite
|
Sign up to set email alerts
|

Minimally‐invasive dental anesthesia: Patients' preferences and analysis of the willingness‐to‐pay index

Abstract: Computer-controlled systems for local anesthesia represent a relevant tool for reducing patients' discomfort during dental treatment. The WTP index helps to quantify its relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We found that the majority of the respondents were willing to pay for public dental services in the case of an emergency (79.4%), which is very encouraging. This finding is similar to those of prior studies [ 8 , 10 , 11 , 17 ]. For instance, Al Garni et al [ 8 ] found that 67% of respondents were willing to pay for implants in Riyadh.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the majority of the respondents were willing to pay for public dental services in the case of an emergency (79.4%), which is very encouraging. This finding is similar to those of prior studies [ 8 , 10 , 11 , 17 ]. For instance, Al Garni et al [ 8 ] found that 67% of respondents were willing to pay for implants in Riyadh.…”
Section: Discussionsupporting
confidence: 93%
“…To this end, several studies have been conducted to evaluate the WTP for dental services [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Among these studies, to the best of our knowledge, only a few were devoted to the KSA [ 8 , 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a computer-controlled delivery device seems to achieve more diffusion of the anesthetic solution than manual syringe (11). Overall, the use of a computerized anesthesia system seems to be preferred as it can reduce disruptive behavior in children (3) and pain during injection (11,17,22). A prospective cohort study (22) reported that more than a half of the patients included would even pay additionally to be anesthetized by a minimally invasive system, thus confirming their positive experience respect to traditional injection.…”
Section: Discussionmentioning
confidence: 99%
“…Different methodological approaches were used to determine WTP, e.g., bidding game, and payment card method, with closed [e.g., Christell et al (2019) [151]], and open [e.g., Tianviwat et al (2008) [152]] response options. Re et al [153][154][155], reported patients would be willing to pay an additional fee to receive a particular treatment. According to McKenna et al (2016) [156], there is a strong WTP regarding basic and functional treatments.…”
Section: Willingness-to-pay In Dental Carementioning
confidence: 99%